The passion of Perpetua and Felicitas as an adapted apocalypse / A paixão de Perpétua e Felicidade como um apocalipse adaptado - Gonzalez, Eliezer (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2013)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-AU JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; –> <!–[endif] –> <!–StartFragment–> The resonances of the language and imagery of the Passion of Perpetua with Jewish apocalyptic literature has long been recognized. A comparison of the morphological features of the Passion of Perpetua with those of apocalyptic literature reveals that they share the same features. Even more fundamentally, key aspects of the social roles which the Passion of Perpetua played within the Carthaginian and North African Christian communities are analogous with the social roles that have been postulated for Jewish apocalyptic literature. The Passion of Perpetua therefore displays the signs of having been written as an adaptation and application of the Jewish apocalyptic texts to the specific challenges faced by the early North African Christian communities. Resumo As ressonâncias da linguagem e do imagético da Paixão de Perpétua com a literatura apocalíptica judaica são há muito reconhecidas. Uma comparação das características morfológicas da Paixão de Perpétua com aquelas da literatura apocalíptica revela que ambas partilham das mesmas características. Mais importante ainda, há aspectos-chave dos papéis sociais desempenhados pela Paixão de Perpétua na comunidade cartaginense e nas comunidades cristãs norte-africanas que são semelhantes aos papéis sociais que têm sido postulados para a literatura apocalíptica judaica. Portanto, a Paixão de Perpétua apresenta sinais de ter sido escrita como uma adaptação e aplicação dos textos apocalípticos judaicos aos desafios específicos enfrentados pelas primitivas comunidades cristãs norte-africanas. <!–EndFragment–>